Role of Wind Energy in Achieving Global Carbon Neutrality: Challenges and Opportunities - Goyal Vishal; Aishwarya M.; Cenate C F Theresa; Varghese Juvitha; Marathe Ashutosh; Bhagat Gorakh P.; Hemalatha (E3S Web of Conferences)
Wind energy is crucial in the worldwide shift towards carbon neutrality, providing a clean, sustainable, and more and more affordable substitute for fossil fuels. This study examines the present state of wind energy on a global scale, its role in mitigating carbon emissions, and the obstacles that impede its extensive implementation. Primary obstacles are financial limitations, incorporation into the power grid, ecological considerations, and governmental laws. Nevertheless, the progress in turbine design, the untapped potential of offshore wind, and the emergence of hybrid systems offer substantial prospects for expanding wind power. The article also analyzes the economic and social advantages of wind energy, including the creation of jobs and the development of rural areas, while emphasizing the significance of supportive policy frameworks. By tackling these obstacles and harnessing advancements, wind energy can play a pivotal role in attaining worldwide carbon neutrality objectives by 2050. The conversation ends with a plan for future expansion and emphasizes the crucial importance of international cooperation in fully achieving the promise of wind energy.